2019
DOI: 10.1073/pnas.1909989116
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental mutation of giant ankyrin-G disrupts a core mechanism for axon initial segment assembly

Abstract: Giant ankyrin-G (gAnkG) coordinates assembly of axon initial segments (AISs), which are sites of action potential generation located in proximal axons of most vertebrate neurons. Here, we identify a mechanism required for normal neural development in humans that ensures ordered recruitment of gAnkG and β4-spectrin to the AIS. We identified 3 human neurodevelopmental missense mutations located in the neurospecific domain of gAnkG that prevent recruitment of β4-spectrin, resulting in a lower density and more elo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 52 publications
1
55
0
Order By: Relevance
“…In contrast, staining of hippocampal sections of βII‐spectrin KO mice of unreported age with a βIV‐spectrin‐specific antibody, also an AIS marker, detected significant AIS fragmentation and increased area of immunoreactivity (Galiano et al, ). It is worth noting that loss of βII‐spectrin, both in vivo and in vitro, results in over a 40% increase in βIV‐spectrin‐∑VI (Lorenzo et al, ), which is critical for the maintenance of the AIS (discussed below; Yang, Walder‐Christensen, Lalani, et al, ), and may explain some of the observed differences between the studies. Given the importance and multifaceted roles of βII‐spectrin, it will important to further assess how it might impact AIS morphology, composition, and function.…”
Section: Subcellular Distribution and Nano‐ And Micro‐assembly Of Neumentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, staining of hippocampal sections of βII‐spectrin KO mice of unreported age with a βIV‐spectrin‐specific antibody, also an AIS marker, detected significant AIS fragmentation and increased area of immunoreactivity (Galiano et al, ). It is worth noting that loss of βII‐spectrin, both in vivo and in vitro, results in over a 40% increase in βIV‐spectrin‐∑VI (Lorenzo et al, ), which is critical for the maintenance of the AIS (discussed below; Yang, Walder‐Christensen, Lalani, et al, ), and may explain some of the observed differences between the studies. Given the importance and multifaceted roles of βII‐spectrin, it will important to further assess how it might impact AIS morphology, composition, and function.…”
Section: Subcellular Distribution and Nano‐ And Micro‐assembly Of Neumentioning
confidence: 99%
“…However, the DAR999AAA mutation in 480‐kDa ankyrin‐G, which eliminates the canonical binding of ankyrin‐G to βII‐spectrin (He et al, ; Kizhatil et al, ), has no effect on 480 kDa ankyrin‐G or βIV‐spectrin clustering at the AIS (Jenkins et al, ), suggesting that either the site for βIV‐spectrin binding is not conserved in 480‐kDa ankyrin‐G and/or additional coupling mechanisms between these two partners exist (Jenkins et al, ). On the other hand, introduction of the Y1901A mutation (corresponding to the Y1874A mutation in βII‐spectrin that disrupts binding to ankyrin‐G) in βIV‐spectrin‐∑I, the full‐length βIV‐spectrin splice variant, fails to restore AIS morphology and the clustering of 480‐kDa ankyrin‐G, and its AIS partners, in βIV‐spectrin null neurons (Yang, Walder‐Christensen, Lalani, et al, ). Surprisingly, deficits in AIS morphology and molecular composition of βIV‐spectrin null neurons can be rescued in vitro with βIV‐spectrin‐∑VI, the other βIV‐spectrin isoform present in the AIS, which lacks the actin binding site plus the first nine spectrin repeats, but retains the ankyrin‐G binding site and a PH domain (Yang, Walder‐Christensen, Lalani, et al, ).…”
Section: Subcellular Distribution and Nano‐ And Micro‐assembly Of Neumentioning
confidence: 99%
See 3 more Smart Citations